2022
DOI: 10.3390/su142416578
|View full text |Cite
|
Sign up to set email alerts
|

Extruded Corn Snacks with Cricket Powder: Impact on Physical Parameters and Consumer Acceptance

Abstract: Edible insects are more and more widely researched and presented as a good source of nutrients. Among the available raw materials, cricket powder (CP), obtained from roasted and crushed crickets, deserves attention because it can be used as an ingredient in many food products. The aim of this study was to determine the effect of CP addition on the physical and sensory properties of extruded corn snacks. In the extrusion process, five variants of corn snacks were produced with 2%, 4%, 6%, and 8% additions of CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Control corn cookies had the highest a w (0.51) and 20% nettle corn cookies had the lowest (a w = 0.31). The results are consistent with those of Ruszkowska et al (2022), who obtained water activity ranging between 0.311 and 0.386 when cricket powder was incorporated into extruded corn snacks.…”
Section: Activity Of Cookies During Storagesupporting
confidence: 91%
“…Control corn cookies had the highest a w (0.51) and 20% nettle corn cookies had the lowest (a w = 0.31). The results are consistent with those of Ruszkowska et al (2022), who obtained water activity ranging between 0.311 and 0.386 when cricket powder was incorporated into extruded corn snacks.…”
Section: Activity Of Cookies During Storagesupporting
confidence: 91%
“…Despite that most of the consumers still do not accept insects' consumption [7], insects, as a food ingredient, are an alternative that is likely to increase consumer's acceptance [8][9][10][11]. Indeed it as reported that the inclusion of insects in the main recipe of products significantly improves their acceptability, and these changes are associated with the modification of volatile compound profiles of the products [12,13], among other technological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-expanding population, potentially surpassing 11 billion in approximately 30 years, consistently drives the exploration for fresh food sources and innovative production methods [1]. The observed need to increase food production to meet the demand for essential nutrients prompts the search for possible solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The observed need to increase food production to meet the demand for essential nutrients prompts the search for possible solutions. Also, the increasing costs of food production, climate change, environmental pollution, limited freshwater resources, affect this trend [1][2][3]. This trend is related to the pursuit of alternative and sustainable food sources rich in the complete set of proteins needed in the human diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation